The Potential for Non-Fungible Tokens (NFTs) in Brand Marketing - Sawu, Rohini (University of the Witwatersrand, Johannesburg, 2023)
This research is an exploration of the potential role of non-fungible tokens (NFTs) in brand marketing communications in a South African context
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Non-fungible tokens; NFTs, brands; Marketing; Marketing communications; Brand equity; IMC; Consumer packaged goods; CPG; UCTD; SDG-8: Decent work and economic growth